A20/Tumor Necrosis Factor α-Induced Protein 3 in Immune Cells Controls Development of Autoinflammation and Autoimmunity: Lessons from Mouse Models - Das, Tridib; Chen, Zhongli; Hendriks, Rudi W.; Kool, Mirjam (Frontiers in Immunology, 2018)
Immune cell activation is a stringently regulated process, as exaggerated innate and adaptive immune responses can lead to autoinflammatory and autoimmune diseases. Autoinflammation and autoimmunity are mediated by aberrantly activated immune cells, either innate or adaptive immune cells. Perhaps the best-characterized molecular pathway in immune cell activation is the nuclear factor-κB (NF-κB) signalling pathway leading to transcription of numerous pro-inflammatory and cell-survival genes. NF-κB activation is tightly controlled by several mechanisms, including the key regulatory zinc-finger (de)ubiquitinating enzyme A20/TNFAIP3. Single nucleotide polymorphisms (SNPs) in the vicinity of the TNFAIP3 gene are associated with a spectrum of chronic systemic inflammatory diseases, indicating its clinical relevance. Mice harboring targeted cell-specific deletions of the Tnfaip3 gene in innate immune cells like macrophages spontaneously develop autoinflammatory disease. In contrast, when immune cells involved in the adaptive immune response, like dendritic cells or B-cells are targeted for A20/TNFAIP3 deletion, mice develop spontaneous inflammation that resemble human autoimmune disease. Therefore, more knowledge on A20/TNFAIP3 function in innate and adaptive immune cells is beneficial in our understanding of autoinflammation and autoimmunity. Using the above mentioned mouse models, novel A20/TNFAIP3 functions have recently been described such as control of necroptosis and inflammasome activity. In this review, we discuss the function of the A20/TNFAIP3 enzyme, and its critical role in various innate and adaptive immune cells. Lastly, we discuss the latest findings on A20/TNFAIP3 SNPs in human autoinflammatory and autoimmune diseases and address that genotyping of TNFAIP3 SNPs may guide treatment decisions.